Smart nanomaterials—environmental safety, risks, legal issues, and management - Vydiam K.; Mukherjee S. (My University, 2025)
Smart nanomaterials are being explored for their multifunctional applications in different fields including biological and environmental applications since the last two decades. Nanomaterials including polymeric, liposomes, and organic and inorganic types are being explored for different applications such as anticancer, imaging, diagnostics, antibacterial, biosensing, theranostics, etc. However, with growing utilization, and lack of regulatory details; the safe usage of these nanomaterials has become of the greatest importance. The lack of available data from research laboratories and strict regulations created by regulatory agencies have caused great challenges for these nanomaterials to be clinically approved and usable. Over the last 5 years, researchers are putting more effort to collect details on the physical, chemical, and biological properties of these smart nanoparticles, which will help to facilitate easier transitions of these drugs to clinics from the bench side. In this chapter, we will focus on highlighting various safety, risks and regulatory aspects of these nanomaterials in detail. © 2023 Elsevier Inc. All rights reserved.